XML Compression System on Smartcard Case Study of Medical Record Data - Ahmad Habib; Muhamad Firdaus; Muhammad Syarifuddin (Universitas Islam Sultan Agung, 2018)
In the medical service at the practice site as well as in the standard hospital, the physician keeps a record of the patient's information in a file known as the medical record. The drawback to this file is the availability of unreliable data. Where a patient's medical record should be searched one by one in a particular file. In this research, we will create a medical record application system with XML compression feature with tag method (firstchild,sibling)* data combined with Bzip2 method on ACOS smartcard storage media. The results obtained are, the ratio of file size written on smartcard media is smaller than the files that are not compressed. The average ratio ranges from 14.04% with sampling data from 500 - 31000 bytes. Average reading time is 5.71 seconds, and the writing process is about 11.69 seconds.